Sharia Fintech in Digital Transformation: Driving the Growth of the Halal Industry in Indonesia - Anis Ni’am Imana (Journal of Economics and Social Sciences (JESS), 2025)
Digital transformation has brought substantial changes the peoples lives. Financial technology or fintech has become a pioner of the economy in Indonesia, especially for halal industry sector. Sharia fintech comes with digital innovations combined with the principles of sharia, which can opportunities and potential for economic growth an development. The purpose of this study is to analyze the role of sharia fintech in digital transformation that can boostt the halal industry sector. This study uses a descriptive method with a review of relevant literature. Data was collected forom journals, books, and research reports. The findings of this study are that sharia fintech contributes greatly in driving the growth of halal industry in Indonesia through the contracts available on platform digital such as murabahah, mudharabah, ijarah, investment and ZISWAF, increasing trend of halal lifestyle, so the government support through PBI, PJOK regarding digital service, and DSN-MUI fatwas on the regulation of sharia contracts and also ASFI which regulates the availability on sharia digital platforms that can support the halal industry in the halal food and drink, trorism, pharmaceuticals, and fashion. Sharia fintech is increasingly good its position, where data shows that around 70% of loand in the UMKM sharia cluster online.